EFFECT OF SOIL DEPTH ON THE DEGREE OF SWEET POTATO WEEVIL INFESTATION - Burdeos, AT; Gapasin, DP (Annals of Tropical Research, 1980)
Soil depth affected the degree of sweet potato weevil infestation. Highest weight of infested tubers was obtained from the control (without soil added) while the lowest weight was obtained at 26 cm soil depth. Weevil population in tubers showed a similar trend. No infestation was recorded at 29 cm depth. Results show that soil depth significantly affected the non-infested tuber yield and the degree of sweet potato weevil infestation. The greater the depth, the fewer the infested tubers. This implies that burying tubers deeper, such as hilling up at the base of sweet potato during tuber formation, can reduce weevil infestation.